2016
DOI: 10.1080/01616412.2015.1114741
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel mutations of theCLCN1gene for myotonia congenital in China

Abstract: Genetic screening identified nine CLCN1 mutations among the eight patients, including two missense, three nonsense, two insertion, and two deletion mutations. The patients showed typical myotonia and muscle hypertrophy. In contrast to the previous studies, secondary dystonia, joint contracture, and abnormal cardiac activity were also observed. Patients with novel mutations did not show any new muscle pathology compared with established mutations. Disscussion: Molecular genetics analysis offers an accurate meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In our study, PMC with the L689F variant was accompanied by progressive muscle weakness, which was characterized by difficulty in climbing stairs, and similar muscle weakness has been reported for the same variant ( 7 ). In eight patients, myotonia could cause secondary dystonia, which could lead to secondary joint contractures during the development of the disease ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, PMC with the L689F variant was accompanied by progressive muscle weakness, which was characterized by difficulty in climbing stairs, and similar muscle weakness has been reported for the same variant ( 7 ). In eight patients, myotonia could cause secondary dystonia, which could lead to secondary joint contractures during the development of the disease ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing showed that 19 different pathogenic variants in the CLCN1 gene were identified in 17 MC patients, including 14 missense, four frameshift, and one non-sense variants. Among them, c.795T>G (p.D265E) was a novel missense variant, and the other 18 variants had previously been reported (6,12,(15)(16)(17). Combining this with family history, 10 patients with one heterozygous variant and seven patients with two compound heterozygous variants were diagnosed with DMC and RMC, respectively.…”
Section: Genetic Analysismentioning
confidence: 94%
“…While some researchers reported that cardiac abnormalities such as accompanying arrhythmia, pre-excitation syndrome, or left ventricular enlargement were observed in cases with MC 10 but others reported that there was no cardiac problem in cases with MC 11 , 12 . According to inheritance pattern of the disease, family members of our case also had c.1886T>C, (p.Leu629Pro) alteration in CLCN1 gene with autosomal recessive congenital myotonia, too.…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to functionally analyze stop codon-forming mutations beyond Y686*, as this could provide evidence of the location in which the protein starts being functional. A clue about this is provided by the mutation Q788*: although it has not been functionally characterized, it was described that it behaves in a dominant manner [50], likely due to a dominant-negative effect, where the full ClC-1 structure is modified by the interaction of wild-type ClC-1 and an altered ClC-1 structure, affecting thereby the chloride conductance in the patients.…”
Section: Channel Disruptionmentioning
confidence: 99%